2015
DOI: 10.1007/jhep05(2015)021
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz quasinormal modes and relaxation from holography

Abstract: We obtain relaxation times for field theories with Lifshitz scaling and with holographic duals Einstein-Maxwell-Dilaton gravity theories. This is done by computing quasinormal modes of a bulk scalar field in the presence of Lifshitz black branes. We determine the relation between relaxation time and dynamical exponent z, for various values of boundary dimension d and operator scaling dimension. It is found that for d > z + 1, at zero momenta, the modes are underdamped, whereas for d ≤ z + 1 the system is alway… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 44 publications
7
59
1
Order By: Relevance
“…Note first that for the cases where z ≥ d − 1, there are no oscillations, the system is overdamped. This will be more clear when we look at the QNMs, and is in agreement with [25].…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Note first that for the cases where z ≥ d − 1, there are no oscillations, the system is overdamped. This will be more clear when we look at the QNMs, and is in agreement with [25].…”
supporting
confidence: 82%
“…The value α ¼ 1 can be found from AdS 3 , where one can show analytically that τ ¼ 1=ð4πT 0 Þ [25,29,30]. Curiously, this is not the minimal value of the relaxation time, which instead sits at α ≈ 0.847 227 and reads τ ≈ 0.989 002=ð4πT 0 Þ.…”
Section: H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…The matter is parameterized by scalar fields minimally coupled to gravity. Then we obtain numerically the quasinormal frequencies (QNFs) for scalar fields by using the improved AIM [17], which is an improved version of the method proposed in [18,19] and which has been applied successfully in the context of quasinormal modes (QNMs) for different black hole geometries (see for instance [17,[20][21][22][23][24][25][26][27]). Then we study their stability under scalar perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Then we study their stability under scalar perturbations. We focus our study on the dependence of the dynamical exponent, the nonlinear expo-nent, the angular momentum, and the mass of the scalar field in obtaining overdamped and non-overdamped quasinormal frequencies, mainly, motivated by a recent work, where the authors showed that for d > z + 1, at zero momenta, the modes are non-overdamped, whereas for d ≤ z + 1 the system is always overdamped [24]. This is contrary to other Lifshitz black holes where the QNFs show the absence of a real part [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The QNFs have been calculated by means of numerical and analytical techniques; the QNMs of Lifshitz black holes under scalar field perturbations have been studied in [23,[79][80][81][82][83][84][85][86][87][88][89], and generally the scalar modes of Lifshitz black holes are stable. Non-relativistic fermion Green's functions in fourdimensional Lifshitz spacetime with z = 2 were studied in [90] by considering fermions in this background and a nonrelativistic (mixed) boundary condition, and it was shown that the Green's functions have a flat band.…”
Section: Introductionmentioning
confidence: 99%